'I feel like I'm in poverty. I don't do much outside of work other than survive': In-work poverty and multiple employment in the UK. (August 2022) - McBride, Jo; Smith, Andrew
This article argues for the need to reconsider the changing nature of in-work poverty (IWP). In doing so, the authors present evidence not included in current debates or statistics, of people working in more than one job, yet still experiencing IWP. Using the dynamic theory of poverty and a qualitative approach, the authors identify various structural constraints that sustain cycles of IWP. This highlights the multidimensionalities of poverty, incorporating the temporalities, types and depths of IWP. The evidence demonstrates how poverty is experienced and individualised and also how it is created and sustained through paid work, rather than being challenged by it.